TP-NER: A named entity recognition dataset of target and precursor named entities for high-temperature steel - Miah, Md Saef Ullah; Sulaiman, Junaida; Ferdous, I. U.; Sarwar, Talha (2022)
This dataset contains target and precursor-named entity data for high-temperature steel-related texts from published papers in IOB format. This dataset has been annotated and verified by domain experts. This dataset has 249304 rows and 3 columns. The sentence ID is in the first column, the tokens are in the second column, and the target or precursor tag is in the third column. This dataset contains data for five annotated documents among 25 documents.